Determinan Penerapan Protokol Kesehatan Pencegahan Covid-19 pada Staf Dinas Penanaman Modal dan Pelayanan Satu Pintu Aceh - Teuku Bakhtiar; Eddy Azwar; Vera Nazhira Arifin (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
The disease caused by the corona virus, otherwise known as COVID-19, is a new type that was discovered in 2019 and has never been identified as attacking humans before. This study aims to identify the behavioral determinants of implementing the Covid-19 Prevention Health Protocol in Staff of the Aceh Investment and One-Stop Service Office. This type of analytic descriptive research with a cross sectional design. The population in this study were all staff of the Aceh Investment and One-Stop Service Office, totaling 48 people. The research sample is the total of the population. Data collection was carried out from 12 and 13 September 2022. Data collection was by means of a questionnaire. Data analysis used statistical tests with Chi-square with Î± 0.05. From the results of the study it was found that they were not compliant with health programs (22.9%), male sex (58.3%), lack of knowledge (18.9%), positive attitude (31.3%), low confidence (29, 2), media access to information does not exist (14.6%) and does not comply with regulations (18.8%). From the results of statistical tests, it can be concluded that there is a relationship between knowledge (p value = 0.002), attitude (p value = 0.002), belief (p value = 0.0001) and access to information media (p value = 0.004) and the implementation of the Covid Prevention Health Protocol -19 On the staff of the Aceh Investment and One Stop Service Service. It is hoped that the staff of the Aceh Investment and One Stop Services Service can increase their knowledge about COVID-19 and attitudes about COVID-19 so that they can improve their behavior in preventing COVID-19 by accessing the right information.